Filsafat Hukum Ekonomi Syariah Pada Akad-Akad Perbankan Syariah Di Indonesia - Surury, Nurul Azizah; Badry, Ahmad Ibrahim (Innovative: Journal Of Social Science Research, 2024)
Contracts in sharia economics depend on a legal philosophical foundation. The philosophy of sharia economic law shows the nature of an economy that is oriented towards spiritual and humanitarian aspects. The spiritual dimension places God as the main focus in human economic activities which ultimately results in economic behavior that prioritizes human values such as benefit, justice and mutual benefit. This research uses qualitative methods through library research by analyzing and collecting data through understanding and learning theories from various related sources. Data was collected through searching for relevant books, journals and research. This research aims to analyze sharia banking contracts based on the philosophy of sharia economic law. Sharia economic principles include metaphysical, epistemological, moral and spiritual aspects. This shows that sharia economics does not only focus on normative analysis, but also pays attention to in-depth philosophical aspects. Contracts in sharia economics are very complex, it is hoped that further development can be carried out in innovative sharia economic practices and in accordance with Islamic principles.